2015
DOI: 10.1007/978-3-319-22389-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation and Social Participation: A Case Study in Public Security in Brazil

Abstract: Abstract. In Brazil the predominant culture is not the appreciation of community participation in solving local problems. However the solutions presented by authorities are not the most efficient, and do not solve the problems. Nowadays, however, with the use of information and communication technologies associated with open innovation and gamification, citizens began to actively participate in decision-making processes of government. In this context, this study aims to describe the project of the 8th State Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
14

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 9 publications
0
20
0
14
Order By: Relevance
“…Nonetheless, governmental presence in research is still observed [4,8,9,11,38,53,68,71]. In fact, although such reports are rare, some of the research has led to actual policy implementations [69]. Such outcomes should be highlighted to increase citizens trust in governments and research.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Nonetheless, governmental presence in research is still observed [4,8,9,11,38,53,68,71]. In fact, although such reports are rare, some of the research has led to actual policy implementations [69]. Such outcomes should be highlighted to increase citizens trust in governments and research.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…InnoCentive focuses on producing open innovation for contracting companies, as declared in its core message: "Innovate with InnoCentive" 5 . This platform has also been used in the public sector, supporting the challenge.gov initiative; as a pioneer for governments, such as the Brazilian government that uses idea challenges to generate innovations in vocational and technological education and public health [15]; in the management of natural resources and sustainability [16]; and for the improvement of public security [17].…”
Section: Innocentive Crowdstormingmentioning
confidence: 99%
“…gov platform created by U.S President Obama government to challenge citizens to engage to solve public problems, which are traditionally the responsibility of various governmental agencies (Linders, 2012). In Brazil, the idea-sending platform (Prêmio Ideia) can be highlighted by its use by public institutions to capture local knowledge to solve problems (Souza et al, 2014;Santos, 2015;Martins and Souza Bermejo, 2016). On this platform, the institution that promotes the challenge of ideas launches an issue of public interest online and asks for citizen participation to find a solution.…”
Section: Social Participation and Collective Production Of Ideasmentioning
confidence: 99%
“…In exchange for participation, it offers a (usually cash) prize, for the idea that is considered the best by the other participants and by the proposing institution. Santos (2015) details the case of the Idea Prize platform used by the Military Police of Minas Gerais and presented the ideas that were sent by citizens and that became visible and were applied by the institution, such as the use of unmanned aerial vehicles (drones) for monitoring and implementing security networks (Santos, 2015). Thus, the public institution opens itself up to receive ideas from the community and social participation involves active participation of the citizens in public decisions and actions, in the life of the community and in the issues of interest of their communities (Medeiros and Borges, 2007).…”
Section: Social Participation and Collective Production Of Ideasmentioning
confidence: 99%
See 1 more Smart Citation